2015
DOI: 10.1089/chi.2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

Parental Control, Nurturance, Self-Efficacy, and Screen Viewing among 5- to 6-Year-Old Children: A Cross-Sectional Mediation Analysis To Inform Potential Behavior Change Strategies

Abstract: Background: Children's screen viewing (SV) is associated with higher levels of childhood obesity. Many children exceed the American Academy of Pediatrics guideline of 2 hours of television (TV) per day. There is limited information about how parenting styles and parental self-efficacy to limit child screen time are associated with children's SV. This study examined whether parenting styles were associated with the SV of young children and whether any effects were mediated by parental self-efficacy to limit scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 34 publications
4
58
1
Order By: Relevance
“…An overview of screenbased media use in our sample suggests that TV outweighs all the other screen-based media devices. The amount of time spent watching TV is comparable to that reported elsewhere (Jago, Wood, Zahra, Thompson, & Sebire, 2015), as is the case with the amount of time spent using computers (Veldhuis, van Grieken, Renders, HiraSing, & Raat, 2014). However, children in our study used mobile screen media devices somewhat less than those reported by other authors (Kabali et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…An overview of screenbased media use in our sample suggests that TV outweighs all the other screen-based media devices. The amount of time spent watching TV is comparable to that reported elsewhere (Jago, Wood, Zahra, Thompson, & Sebire, 2015), as is the case with the amount of time spent using computers (Veldhuis, van Grieken, Renders, HiraSing, & Raat, 2014). However, children in our study used mobile screen media devices somewhat less than those reported by other authors (Kabali et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Measurement of parental restrictions in the present study might capture a broader range of strategies, relying on control. Careful discrimination between various control-based strategies used by parents is essential to clarify potential measurement-related sources of discrepancies in findings on parental control-based strategies (including restrictions) and screen time (Jago et al, 2015;Sleddens et al, 2017). Parental restrictions and screen use were measured at the same time point, hence the order in which these variables operate could not be established and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies accounting for child and parental perceptions of parental practices confirmed that parental factors (including parental behaviours, practices, and perceptions) may determine screen use in youth (for review, see Minges et al, 2015). Importantly, the majority of quantitative research investigating links between parental practices and child sedentary behaviours focused on parental perceptions of parental practices, whereas child perceptions of parental practices were not accounted for (Jago, Wood, Zahra, Thompson, & Sebire, 2015;Lloyd, Lubans, Plotnikoff, Collins, & Morgan, 2014;Solomon-Moore et al, 2017).…”
Section: Statement Of Contributionmentioning
confidence: 99%
See 2 more Smart Citations